Ad hoc adaptability in video-calling - Rintel, Sean; O'Hara, Kenton; Yehaneh, Behnaz Rostami (2015)
In this position paper we explore ad hoc adaptability across devices in video-calling. We note the current difficulty of even simple combinations, discuss design issues, briefly report on a study of ad hoc screen mirroring, and note future directions.
ITS'2015 - Workshop on Interacting with Multi-Device Ecologies in the Wild